2020
DOI: 10.1038/s41398-020-0711-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors underlie the association between anxiety, attitudes and performance in mathematics

Abstract: Students struggling with mathematics anxiety (MA) tend to show lower levels of mathematics self-efficacy and interest as well as lower performance. The current study addresses: (1) how MA relates to different aspects of mathematics attitudes (self-efficacy and interest), ability (understanding numbers, problem-solving ability, and approximate number sense) and achievement (exam scores); (2) to what extent these observed relations are explained by overlapping genetic and environmental factors; and (3) the role … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 54 publications
1
21
0
1
Order By: Relevance
“…For example, math-anxious individuals demonstrated general-anxiety-related neuro-physiological responses [ 44 ] and maladaptive threat-related attentional bias [ 45 , 46 ]. Moreover, genetic studies have found that general anxiety explained 9% of the total variance in math anxiety [ 34 , 47 ], and general and math anxiety shared about 20% of their genetic variance [ 48 ]. In a similar vein, a longitudinal path model showed general anxiety disorder was a significant predictor of math performance [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, math-anxious individuals demonstrated general-anxiety-related neuro-physiological responses [ 44 ] and maladaptive threat-related attentional bias [ 45 , 46 ]. Moreover, genetic studies have found that general anxiety explained 9% of the total variance in math anxiety [ 34 , 47 ], and general and math anxiety shared about 20% of their genetic variance [ 48 ]. In a similar vein, a longitudinal path model showed general anxiety disorder was a significant predictor of math performance [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with previous variable-centered studies that suggested an inverse relationship between math anxiety and motivational variables ( Meece et al, 1990 ; Ahmed et al, 2012 ). A recent study employing ACE model on 3,410 twins showed negative correlations between math anxiety and two math attitude variables, interest and self-efficacy, both phenotypically (−0.45) and genetically (−0.7) ( Malanchini et al, 2020 ). Interestingly, with a person-centered approach, our study found an exceptional subgroup, class 1, of which the students with medium math interest, instrumental motivational to learn, and math self-concept had high math anxiety and low rather than medium perceived control in math.…”
Section: Discussionmentioning
confidence: 99%
“…They found that math anxiety impedes advanced memory-based strategy use and impairs math achievement by diminishing the use of advanced memory-based strategies. Further, a recent twin study confirmed a negative correlation between math anxiety and performance, which is attributed to both environmental and genetic factors quantitatively ( Malanchini et al, 2020 ).…”
Section: Introductionmentioning
confidence: 93%
“…Проведенные многомерные количественные генетические анализы показали, что примерно 75 % дисперсии математической тревожности могут быть объяснены генетическими факторами. Был сделан вывод о том, что так как математическая тревожность напрямую связана с успехами в математике [11], а генетические характеристики влияют на математическую тревожность, то прослеживается связь между генетикой и способностями к математике [12].…”
Section: Introductionunclassified